GREEN TENSOR OF MOTION EQUATIONS OF TWO COMPONENTS BIOT’S MEDIUM BY STATIONARY VIBRATIONS - Alexeyeva L.A.,; Kurmanov E.B., (Academic Scientific Journal of Computer Science, 2019)
Here processes of wave propagation in a two-component Biot’s medium are considered which are generated by periodic forces actions. By use Fourier transformation of generalized functions, the Green tensor - a fundamental solutions of oscillation equations of this medium has been constructed. This tensor describes the process of propagation of harmonic waves of a fixed frequency in spaces of dimension N = 1,2,3 under the action of power sources concentrated at the coordinates origin, described by a singular delta -function. Based on it, generalized solutions of these equations are constructed under the action of various sources of periodic perturbations, which are described by both regular and singular generalized functions. For regular acting forces, integral representations of solutions are given that can be used to calculate the stress-strain state of a porous water-saturated medium